The Importance of Analyzing the Needs of School Administration Personnel in Managing Human Resources - Faradiba, Nabil Aurora; Burhanuddin, Burhanuddin; Triwiyanto, T (Universitas Negeri Malang, 2024)
This research focuses on the importance of analyzing the needs of school administration personnel in managing human resources to support the success of the educational process. Through literature studies, this study analyzes various aspects related to the management of school administration personnel ranging from needs analysis, planning, recruitment, competency development, to performance evaluation. Currently, there is still a shortage of school administration personnel and even their performance competence. Therefore, it requires effective and efficient management of school administration personnel, including needs analysis, careful planning, and continuous competency development. The optimal performance of school administration personnel can contribute significantly to improving the quality of education in schools. This study uses a descriptive qualitative method with a literature study approach. Data is obtained from various sources, such as scientific journals and articles. This article provides guidance for schools in improving the competence and management of school administration personnel through a planned and systematic approach.